EFEK PERTAHANAN TUBUH : INFLAMASI SETELAH LATIHAN - Muhammad Yusrin Al Gifari; Yanasta Yudo Pratama (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
The immune system is the body's defense effort to prevent and eliminate pathogens. Inflammation is a form of the body's response to the damage that occurs. Acute and chronic effects of exercise on the immune system. Moderate-intensity exercise enhances immune function responses, strengthens anti-oxidant capacity, and reduces inflammatory events. Exercise-induced enhancement of immune function plays a role in countering immunosenescence and the development of chronic disease. The method used in this paper is the literature reviewed using the Google Scholar, Pubmed, and Research Gate database with the topic "Body Defense and Inflammation for Exercise". The search keywords used in the database are keywords used to expand or specify searches so that they can make it easier to determine the articles or research journals used. Literature Review Selection using Inclusion and Exclusion Categories and by taking into account the interrelationships between keywords. Inflammation is a signal that indicates the occurrence of injury to the tissue as a result of exercise. Exercise is known to be able to alter metabolism, which induces an anti-inflammatory response. Proper exercise will determine the process of tissue repair and maintain homeostasis in the body. Exercise causes inflammation caused by tissue damage. The inflammatory response is part of the tissue regulatory process and is considered a method of the body's defense process.